Market and marketing information of Bodija plank market in Ibadan metropolis, Ibadan, Oyo State, Nigeria (2013)
This study assessed the characteristics of the market and marketing information of Bodija Plank market, Ibadan with a view to suggest ways for the market to be more transparent and efficient. Twenty sawnwood traders were randomly selected from five of the nine plank market zones for administration of questionnaire. Thus primary data were collected from 100 randomly selected respondents. Data collected were analyzed using descriptive statistics. The Bodija plank market which covers a total land area of 0.12km2is made up of nine zones comprising 66 blocks and 1868 stalls. Most of the respondents (78.6%) were males, 71.6% were between the age of 30 and 49 years, 93.9% was married, 57.3% had secondary education while 62.3% had been involved in sawnwood trade between 10 and 29 years. The prevailing type of differentiation in the plank market is the horizontal product differentiation which is linked with strength, colour, species, size, function and method of production. Thus 26 wood species, six sizes and two production methods were identified as sources of product differentiation in the market. Therefore 74.5% and 11.2% of the respondents identified strength as well as colour and strength as the main reason why some species are in relatively high demand. The structure of the market is somewhat monopolistic competitive in nature because of the existence of the Oyo State Plank Market Association which determines who can sell sawnwood in the market as attested by 81.6% of the respondents, thereby constituting an entry barrier to the plank market. All the respondents made use of phones to collect and disseminate marketing information, 80.6% were aware of the internet, but only 7.1% made use of internet to collect and disseminate marketing information. Prices and availability of sawnwood were the essential marketing information that the sawnwood traders always look for as reported by 56.1% of the respondents while market and customers were respectively reported by 35.7% and 37.8% of the respondents as the main sources of marketing information. Furthermore, 73.5% of the respondents posited that most of the sawnwood sold in the market are from outside Oyo State. Promotion of transparent and efficient marketing of sawnwood in Bodija market will require first the production and use of wood quality manual which contains objective measurable wood quality parameters for ranking wood species in order of suitability for specific purposes and second the development by forestry related institutions a Marketing Information System (MIS) for sawnwood.